Fabrication and microwave absorption properties of magnetite nanoparticle–carbon nanotube–hollow carbon fiber composites. (January 2015) - Qiu, Jun; Qiu, Tingting
Abstract: Absorbents with "tree-like" structures, which were composed of hollow porous carbon fibers (HPCFs) acting as "trunk" structures, carbon nanotubes (CNTs) as "branch" structures and magnetite (Fe3 O4 ) nanoparticles playing the role of "fruit" structures were prepared by chemical vapor deposition technique and chemical reaction. Microwave reflection loss, permittivity and permeability of Fe3 O4 –CNTs–HPCFs composites were investigated in the frequency range of 2–18 GHz. It was proven that prepared absorbents possessed the excellent electromagnetic wave absorbing performances. The bandwidth with a reflection loss less than −15 dB covers a wide frequency range from 10.2 to 18 GHz with the thickness of 1.5–3.0 mm, and the minimum reflection loss is −50.9 dB at 14.03 GHz with a 2.5 mm thick sample layer. Microwave absorbing mechanism of the Fe3 O4 –CNTs–HPCFs composites is concluded as dielectric polarization and the synergetic interactions exist between Fe3 O4 and CNTs–HPCFs.